Formulation and Evaluation of Microsphere-Encapsulated Topical Gel. - Fotedar, Shivani; Sihare, Mohini (Journal of Neonatal Surgery, 2025)
A superficial fungal infection in immunocompromised persons can cause a variety of illnesses and problems. New topical therapeutic options are urgently needed to treat these fungal infections. The current study aimed to create a stable and effective topical formulation containing itraconazole. Itraconazole, abbreviated ITZ, is an antifungal drug used to treat various fungal infections. It is an FDA-approved new azole antifungal medication that combats fungal infections. Fluconazole should not be taken orally because it has various harmful effects. Fluconazole topical is commercially accessible; because there are no commercially available gel preparations, these formulations are designed to increase patient compliance, and medication dosage should be reduced to avoid undesirable effects such as renal and liver damage. It was a gel that was transformed by changing the polymer ratio. The FT-IR analysis revealed no interactions and confirmed the drug's purity. Between excipients and medication. Gel formulas were utilized to determine medication concentration, pH, antifungal activity, in vitro diffusion, and viscosity, as well as skin pain and activity levels. Some research suggested that oils from medicinal plants could be employed as anti-FLU-resistant C. albicans drugs.